2003
DOI: 10.1021/es0202412
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Degradation of Metalaxyl in Soils:  Chiral Preference Changes with Soil pH

Abstract: Chiral pesticides are often degraded enantio-/stereoselectively in soils. Degradation is typically studied with one or a small number of soils so that it is not possible to extrapolate the findings on chiral preference to other soils. For this study, the fungicide metalaxyl was chosen as a "chiral probe" to investigate its enantioselective degradation in 20 different soils, selected primarily to cover a wide range of soil properties (e.g., acidic/alkaline, aerobic/ anaerobic) rather than to consider soils of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
231
6

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(255 citation statements)
references
References 27 publications
18
231
6
Order By: Relevance
“…It can exist as two enantiomers, R-(-) and S-(+) (Fig. S1), but the fungicidal activity mostly originates from the R-(-) enantiomer [29,30]. Currently, metalaxyl is marketed and used both as a racemic formulation and as R-(-)-single enantiomer-rich product, called Metalaxyl-M.…”
Section: Optical Isomers or Enantiomers Have Practically Identical Chmentioning
confidence: 99%
See 1 more Smart Citation
“…It can exist as two enantiomers, R-(-) and S-(+) (Fig. S1), but the fungicidal activity mostly originates from the R-(-) enantiomer [29,30]. Currently, metalaxyl is marketed and used both as a racemic formulation and as R-(-)-single enantiomer-rich product, called Metalaxyl-M.…”
Section: Optical Isomers or Enantiomers Have Practically Identical Chmentioning
confidence: 99%
“…Currently, metalaxyl is marketed and used both as a racemic formulation and as R-(-)-single enantiomer-rich product, called Metalaxyl-M. Previous studies have indicated that the degradation of metalaxyl in soil is an enantioselective, microbiologically-mediated process, with S-metalaxyl being degraded more rapidly than R-metalaxyl in anaerobic soils and in aerobic soils with pH < 4, and R-metalaxyl being degraded more rapidly than S-metalaxyl in aerobic soils with pH > 5 [9,21,[29][30][31].…”
Section: Optical Isomers or Enantiomers Have Practically Identical Chmentioning
confidence: 99%
“…However, if the adverse effects are caused only by or mostly by the excluded enantiomer, using enantiomer-enriched products may offer great environmental benefits. In addition, studies show that enantioselectivity may closely depend on environmental conditions and may vary significantly even for the same compound (4,14,24,25). Further studies are needed to characterize interactions of environmental factors, such as soil͞sediment properties, vegetation types, redox conditions, and microbial structures, with enantioselectivity in the behavior of chiral pesticides.…”
Section: Enantioselectivity In Degradationmentioning
confidence: 99%
“…In the brain tissue of seals around Iceland, often only (ϩ) ␣-HCH was found; (Ϫ) ␣-HCH was absent, giving indefinitely large ER values (5,13). Enantioselectivity also has been observed under laboratory conditions in the soil degradation of some chiral herbicides and fungicides, including metolachlor, metalaxyl, and dichlorprop (4,8,14).…”
mentioning
confidence: 94%
“…They concluded that the soil and the presence of bacteria that breakdown chemicals are important factors in determining which isomer might become more prominent over time. 89) Based on the comparison of measured and calculated vibrational circular dichroism, the absolute configuration of (Ϫ)-enantiomer of heptachlor (43) (Fig. 10) can be assigned unambiguously as 1R-heptachlor.…”
Section: Chiral Separationsmentioning
confidence: 99%